2009
DOI: 10.1007/s10165-009-0153-5
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of ankylosing spondylitis in an Iranian population of 98 patients

Abstract: The prevalence and pattern of ankylosing spondylitis (AS) can vary from country to country, according to genetic and environmental factors. This study aims to analyze the patterns of disease in a population of Iranian patients with AS. We performed a prospective study (2002-2007) analyzing 98 patients with diagnosis of AS according to the modified New York criteria. Selected patients underwent complete clinical (initial symptom, axial and peripheral involvement, heel enthesitis, extra-articular manifestations)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
3
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 23 publications
(28 reference statements)
3
15
3
2
Order By: Relevance
“…The diagnostic delay in the current study (9.9 years) was much higher than that reported previously for other Middle Eastern populations [14,15,[23][24][25]. However, an Italian study [26] reported a diagnostic delay of approximately 9 years, and another recent study from North This delay in our study can be explained by the lack of rheumatologists, and the lack of awareness among general practitioners and orthopedists about AS, as most of the patients in this series were diagnosed by rheumatologists (84.3%).…”
Section: Discussioncontrasting
confidence: 72%
“…The diagnostic delay in the current study (9.9 years) was much higher than that reported previously for other Middle Eastern populations [14,15,[23][24][25]. However, an Italian study [26] reported a diagnostic delay of approximately 9 years, and another recent study from North This delay in our study can be explained by the lack of rheumatologists, and the lack of awareness among general practitioners and orthopedists about AS, as most of the patients in this series were diagnosed by rheumatologists (84.3%).…”
Section: Discussioncontrasting
confidence: 72%
“…Delay in diagnosis of SpA has been described in women 5,9,10 and in both sexes 6,7,[11][12][13][14][15][16]20,26,27,29,30,32,33,35,38,39,40,44,45,46 , and although Bandinelli 23 observed less diagnostic delay in women than in men, in most of the papers where delay was compared between men and women, it was greater in women 8,17,18,19,21,22,28,31,34,37,41,42,43,47,48 . This implies that patients have had medically unsolved disorders for a long time, have continued searching for a diagnosis and treatment, or are being erroneously diagnosed and managed 49 .…”
Section: Discussionmentioning
confidence: 99%
“…Each of these was individually combined with: (delay OR delayed) AND (sex OR gender OR women OR woman) NOT (psoriatic arthritis). Complemen tary papers potentially eligible were included, a search through snowballing was performed by cross reference, and 16 studies were identified 1,3,[8][9][10][11][12][13][14][15][16][17][18][19][20][21] . Ultimately, 379 identified papers were consulted.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pathologic alterations occur in synovial and cartilaginous joint and in sites of tendon and ligament attachment to bone [1,2].The most common and characteristic initial symptom of AS is chronic low back pain of insidious onset [3]. Most structures and tissues found in the low back, hip and pelvic areas are capable of producing symptoms.…”
Section: Introductionmentioning
confidence: 99%